Observed Workplace Incivility toward Women, Perceptions of Interpersonal Injustice, and Observer Occupational Well-Being: Differential Effects for Gender of the Observer - Miner, Kathi N.; Cortina, Lilia M. (Frontiers in Psychology, 2016)
The present study examined perceptions of interpersonal injustice as a mediator of the relationship between observed incivility toward women at work and employees’ occupational well-being. We also examined gender of the observer as a moderator of these mediational relationships. Using online survey data from 1,702 (51% women; 92% White) employees, results showed that perceptions of injustice partially mediated the relationship between observed incivility toward women and job satisfaction, turnover intentions, and organizational trust. Men reported greater perceptions of injustice than did women the more they observed the uncivil treatment of women at work and the indirect effects of observed incivility toward women on well-being were stronger for men compared to women. Observed incivility toward women also had direct relationships with the occupational well-being outcomes over and above the impact mediated through injustice, particularly for women. Specifically, observing incivility toward female coworkers directly related to lowered job satisfaction and perceptions of safety for female bystanders. In addition, although both male and female bystanders reported heightened turnover intentions and lowered trust in the organization with higher levels of observed incivility toward women, these relationships were stronger for female than male observers. Our findings both replicate and extend past research on vicarious workplace incivility toward women.